(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2024)
A landscape is commonly conceived as an arrangement of items on solid or liquid surfaces. Despite its entanglement with the landscape, the weather condition tends to be overlooked. The liminal case of a thick fog that suppresses the view of the environment challenges this standard understanding. The paper examines the experience of being lost in fog with respect to perceptual, spatiotemporal and emotional aspects. Fog suspends the everyday scopic regime and the inconspicuous ‘immateriality’ of air as medium of perception, distorting the patterns of perception and temporarily installing an own spatiotemporality. Moreover, fog is an atmospheric phenomenon par excellence, a quasi-thing and a quasi-agent that is usually felt as distressing and maleficent yet may trigger a sense of wonder as well. While it is considered a deficit in epistemic issues, nebulosity has a strong aesthetic expressivity, whose sources range from semantic ambiguity to defamiliarization and the transfiguration of the ordinary.